Determinants of Obesity in School Teachers During the COVID-19 Pandemic in the Region of Cempaka Putih West Jakarta Center - Mutia Yuristi Mutia Yuristi; Hermawan Saputra; Rustika Rustika; Desrialita Faryanti (Faculty of Public Health, Sriwijaya University, 2022)
The COVID-19 pandemic (Coronavirus Disease-2019) is a virus of international concern, WHO has declared the COVID-19 pandemic a public health emergency. In Indonesia, one of the efforts to prevent and control COVID-19 is by means of Emergency PPKM. This PPKM policy causes changes in people's lifestyles such as decreased physical activity and changes in diet that can cause obesity. The prevalence of overweight and obesity has increased from year to yea. The purpose of the study was to obtain the determinants of obesity in school teachers during the COVID-19 pandemic in the Cempaka Putih Barat sub-district, Central Jakarta.This study uses quantitative analysis with a cross-sectional design. The population of the study were teachers of SMP, SMA and SMK as many as 165 samples. The sampling technique is purposive sampling using a questionnaire. Data analysis using Chi-Square and Logistic Regression. Univariate results showed that 104 (63,03%) teachers were obese. The results of Chi-Square show that there are between eating patterns, knowledge, attitudes, actions, and genetics. While those that are not related to activity, level of estimation, gender, and age. The results of the multiple logistic regression test showed that there were five variables that were significantly correlated with obesity in teachers, namely actions, genetics, eating patterns, knowledge and attitudes. It is recommended for school teachers to change a healthy lifestyle during the COVID-19 pandemic to prevent the risk of obesity.